Thromboembolic events in people with cancer during the COVID-19 pandemic: case-control study - Vivian Cristina Gama Souza Lima; Paulo Jorge Pereira Alves; Patrícia dos Santos Claro Fuly (Universidade de São Paulo, 2024)
Abstract Objective: to analyze the association between coronavirus disease infection and thromboembolic events in people with cancer in the first year of the pandemic. Method: case-control study carried out by collecting medical records. The selected cases were adults with cancer, diagnosed with a thromboembolic event, treated in the selected service units during the first year of the pandemic. The control group included adults with cancer without a diagnosis of a thromboembolic event. Pearson's chi-square test was applied to verify the association between risk factors and the outcome and logistic regression techniques were applied to identify the odds ratio for the occurrence of a thromboembolic event. Results: there were 388 cases and 440 control cases included in the study (ratio 1/1). Females predominated, who were white, with mean age of 58.2 (±14.8) years. Antineoplastic chemotherapy was the most used treatment and coronavirus disease was identified in 11.59% of participants. In the case group, deep vein thrombosis was more prevalent. Conclusion: the study confirmed the hypothesis that coronavirus disease infection did not increase the chance of thromboembolic events in people with cancer. For the population studied, the factors that were associated with these events were those related to cancer and its treatment.